Analisis Tingkat Bahaya Longsor pada Ruas Jalan Sicincin-Malalak-Balingka dan Ruas Jalan Padang Lua-Maninjau di Kecamatan IV Koto Kabupaten Agam - Ramadhani, Karyn; Triyatno, Triyatno (Lembaga Yasin AlSys, 2025)
This research aims to map the level of landslide danger and analyze the factors that cause landslides in IV Koto District, Agam Regency. The research method uses a quantitative approach with frequency ratios to determine the level of landslide danger and Pearson correlation to analyze the factors that cause landslides in District IV Koto. The research results show that the level of landslide danger is divided into four categories: not dangerous covering 48% (3.868,989 hectares), slightly dangerous 26% (2.033,912 hectares), dangerous 14% (1.137,001 hectares), and very dangerous 12% (949,303 hectares) of total area of ​​the research area. Based on Pearson correlation analysis, the most dominant factor causing landslides in IV Koto District is geology with a positive correlation value of 0.894 to the level of landslide danger, indicating that the geological structure has a very strong influence on landslide events in the area.